THE ABSURD LIFE OF ELLIE CHU IN THE HALF OF IT MOVIE: ALBERT CAMUS'S PERSPECTIVE - Karim, Nuraisyah Puji Ingkan; Sumayah, Sumayah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study examines the reflection of Albert Camus' concept of absurdity in The Half of It, a movie directed by Alice Wu. Through qualitative and descriptive analysis, the research explores the intersection of existential philosophy with contemporary narratives, focusing on the protagonist, Ellie Chu. This study employs thematic and narrative analysis to identify and interpret elements in the movie that reflect absurdism, providing a fresh perspective on the application of Camus' ideas to modern storytelling. Camus’ theory of absurdity, characterized by alienation, the tension between the search for meaning and the indifference of the world, and the act of rebellion, is illustrated in Ellie’s journey. Her experiences include navigating cultural alienation as the only Chinese student in a small town, grappling with her identity and unreciprocated love, and reconciling personal desires with societal expectations. The findings contribute to literary and cultural studies by highlighting how Camus’ absurdity resonates in contemporary narratives, particularly those exploring identity, alienation, the immigrant and LGBTQ+ experience. By analyzing the interplay between philosophical concepts and cinematic representation, the study sheds light on the relevance of absurdism in understanding human struggles within the complexities of modern life